MAKAN SEHAT, TUMBUH CERDAS: PANDUAN PRAKTIS GIZI UNTUK ORANGTUA MODERN - Haniya Haniya; Rachma Hasibuan (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
This study explores the challenges and opportunities in providing optimal nutrition for children in the modern era, characterized by changing dietary patterns, urbanization, and technological advancements. Nutrition is crucial in supporting children's physical growth, cognitive development, and long-term health. The research employs a qualitative approach through systematic literature reviews of recent studies on child nutrition. Findings indicate that digital technologies, such as nutrition tracking apps, significantly enhance nutritional literacy and practices. A holistic approach that integrates local traditions, nutrition education, and digital technology offers sustainable solutions to combat malnutrition. This study recommends adopting digital technologies and evidence-based nutritional education to promote optimal child growth. Its contribution lies in providing a practical guide that integrates multidisciplinary approaches to simplify optimal nutrition delivery for parents.